Comprehensive Clinical Profile of Mal De Debarquement Syndrome - Cha, Yoon-Hee; Cui, Yong Yan; Baloh, Robert W. (Frontiers in Neurology, 2018)
Background: There has there been increasing awareness that post-motion triggered of rocking self-vertigo can last for months or years, a disorder known as Mal de Debarquement Syndrome (MdDS). A similar feeling of oscillating self-motion can occur without a motion trigger in some individuals, leading to controversy about whether motion-triggered (MT) and non motion-triggered (non-MT) symptoms ultimately represent the same disorder. Recognizing the similarities and differences between MT and non-MT MdDS can prevent unnecessary diagnostic testing and lead to earlier and more effective treatments. Methods: Standardized questionnaire assessment and follow-up interviews of individuals with persistent MT or non-MT MdDS (>1 month) examined at a University Dizziness Clinic. Findings: Questionnaires were available on 80 individuals with persistent MT MdDS and 42 with non-MT MdDS. Sex distribution (81% female) and age-of-onset (mean 43.4 yrs+/-12.2 MT; 42.1+/-15.2 yrs non-MT) were comparable between MT and non-MT MdDS (p>0.05). Mean duration of illness was significantly longer in the non-MT group (82.8+/-64.2 mons) than the MT group (35.4+/-46.4 mons) (p<0.001). There was no correlation between trigger type and age of onset or duration of illness for MT MdDS. Improvement with re-exposure to motion (driving) was typical for both (MT=89%, non-MT=64%) but non-MT individuals more frequently had symptoms exacerbated with motion (MT=0%; non-MT=10%). Peri-menstrual and menstrual worsening of symptoms was typical in both MT and non-MT MdDS (each 71%). Both MT and non-MT MdDS exhibited a higher than population baseline prevalence of migraine (23% and 38%, respectively). Benzodiazepines and SSRI/SNRIs were helpful in both subtypes of MdDS (>50% individuals with a positive response). Physical therapy was modestly helpful in the MT (56%) subtype but not in non-MT (15%). Vestibular therapy made as many individuals worse as better in MT and none improved in the non-MT group. Conclusion: General demographic characteristics and exacerbating factors are similar in MT and non-MT MdDS, but there are differences in the duration of illness, effect of motion on symptoms, and response to therapy. Recognizing clinical features of MdDS subtypes may allow for better tailoring of therapy and potentially serve as classification criteria for new clinical designations.